2021
DOI: 10.1177/14778785211061310
|View full text |Cite
|
Sign up to set email alerts
|

Gotta know why! Preliminary evidence supporting a theory of virtue learning as applied to intellectual curiosity

Abstract: Virtue education is gaining popularity in institutions of higher education. Given this growing interest, several theoretical accounts explaining the process of virtue learning have emerged. However, there is scant empirical evidence supporting their applicability for intellectual virtue. In this study, we apply a theory of virtue learning to the development of intellectual curiosity among undergraduates. We find that learning why virtue is relevant and important to one’s education is consistently and moderatel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Previous research has partly substantiated this notion of malleability by showing that thinking dispositions develop over the course of educational experiences (Cacioppo et al, 1996;Colling, et al, 2022). Other work highlights how explicit intellectual character education 1 can improve thinking dispositions (Brant et al, 2020;Orona, 2021a;Orona & Pritchard, 2021). Orona and Pritchard (2021) showed that subjects who participated in a mini-online course improved on NFC and epistemic curiosity from pretest to posttest.…”
Section: The Malleability Of Thinking Dispositionsmentioning
confidence: 91%
See 1 more Smart Citation
“…Previous research has partly substantiated this notion of malleability by showing that thinking dispositions develop over the course of educational experiences (Cacioppo et al, 1996;Colling, et al, 2022). Other work highlights how explicit intellectual character education 1 can improve thinking dispositions (Brant et al, 2020;Orona, 2021a;Orona & Pritchard, 2021). Orona and Pritchard (2021) showed that subjects who participated in a mini-online course improved on NFC and epistemic curiosity from pretest to posttest.…”
Section: The Malleability Of Thinking Dispositionsmentioning
confidence: 91%
“…thinking styles by increasing knowledge about and the salience of such characteristics (Orona, 2021a;Orona & Pritchard, 2021). The general TDI module(s) are explained in greater detail in Orona and Pritchard (2021).…”
Section: Materialmentioning
confidence: 99%
“…To foster or inculcate epistemic virtues at the individual level, various strategies have been proposed for implementation in higher education (Kuntz and Taylor, 2021). For example, Orona et al have reported experimental successes in enhancing virtue learning among undergraduates (Orona, 2021; Orona and Pritchard, 2022; Orona et al, 2023). In an issue of Education Psychologist on “Educational responses to a ‘post-truth’ world: Diverse approaches to improving thinking about scientific issues,” the education sector’s responses to epistemic deficiency are elaborately discussed (Barzilai and Chinn, 2020).…”
Section: Improving Epistemic Virtues and Addressing Epistemic Vices I...mentioning
confidence: 99%
“…Not only are teaching strategies available, but there is growing evidence that intellectual virtues can be developed in students. For example, a recent study by Orona (2021) demonstrated that curiosity can be deliberately cultivated in students with measurable growth. Thus, education for intellectual virtues already has a variety of teaching strategies and growing evidence of its ability to develop intellectual virtues in students.…”
Section: A Response To the Pedagogical Challengementioning
confidence: 99%